The Effect of Audit Coverage, Regulatory Effectiveness and Counseling Effectiveness on Notification Letter Reporting Compliance in Indonesia : - - ZM, Syehabudin (Scientia Integritas Utama, 2024)
Annual PPh reporting for 2018-2022 in Indonesia, which is still in line of 71.10% - 86.80% indicates the need to carry out research on any factors that influence compliance with annual SPH reporting in Indonesia. Based on research using a dual linear regression model using the ordinary least square method, it was concluded that, either partially or simultaneously, audit coverage ratio, effective regulation, and effective approval greatly affect the level of compliance of annual PPh SPT reporting. It is suggested that the government increasingly strengthen tax inspections, produce more effective rules and increasingly increase the inertity of tax clearance against taxpayers in Indonesia.